Modeling urban socio-ecological drivers of human– carnivore coexistence. Issue 1 (12th November 2020) - Lute, Michelle L; Serenari, Christopher; Drake, Michael D; Peterson, M Nils; Jensen, Jennifer; Belyea, Curtis; Olfenbuttel, Colleen; White, Mallory
Abstract: Achieving human–carnivore coexistence is a growing challenge in an increasingly crowded world. In many cases, humans are already sharing landscapes with carnivores, but conditions promoting coexistence are not well understood. Coyotes ( Canis latrans ) are adaptable meso carnivores and their activities increasingly overlap with those of humans in urban environments. Does this overlap constitute coexistence? How do social variables situated within their rightful ecological contexts influence the potential for conflict? In this study, we explore aggregated social and land cover variables contributing to coexistence between humans and coyotes. We surveyed residents in four North Carolina cities on their perceptions, interactions and preferred management actions related to coyotes. We then modeled spatial patterns in urbanite interactions with and perceptions regarding coyotes and investigated how land cover characteristics may correlate with those perceptions. Our results suggest prior interactions and select land cover types may drive human coexistence with coyotes and contribute contextual understanding of urban socio-ecological systems to prevent conflict and effectively promote coexistence. Additional research that expands upon this study and explores spatial as well as temporal dimensions of human–wildlife coexistence is needed in diverse contexts.